Potomac sprout company : starting and growing a business - Thompson, Kenneth R. (London : SAGE Publications: SAGE Business Cases Originals, 2023)
In 2015, Chris and Wesley Yu founded Potomac Sprout Company on a farm in Thurmont, Maryland. The farm was a desirable purchase because of the horse arena included in the property. They converted the large space to the various areas that would be needed to produce a variety of sprouts. Sprouts are products that are considered a "high-risk" food item by the Centers for Disease Control and Prevention (CDC) (Baker, 2018). Potomac Sprout Co. produces organic alfalfa, broccoli, and daikon radish sprouts through a hydroponic process that takes four days from seed to finished sprout.The case first outlines the general challenges an entrepreneur faces, then videos feature Chris Yu discussing these challenges, including food safety protocols needed with his choice of product. Lastly, the case raises questions for the reader to address regarding steps needed to start a successful business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Entrepreneurship -- Case studies; New business enterprises -- Case studies; Strategic planning -- Case studies